HISTORICAL RESEARCH THROUGH COIN HOARDS - Leilani Štajer (Journal of Ancient History and Archaeology)
This discussion highlights the significance of often overlooked coin hoards in historical studies of the Roman Empire. It analyses the problems of incorporating numismatics as a means for studying ancient Roman history. The main part of the discussion focuses on the reliability level of hoard analysis and the possible pitfalls that lead to an insufficiently critical interpretation. In the example of two fourth-century Roman hoards from Slovenia, the Emona and the Čentur hoards, the author tries to show what such studies can bring, and with which challenges historians are faced with while studying coin hoards. She also explores how new approaches to studying coin hoards could help to integrate their studies into the study of classical history.